Borrelia Diversity and Co-infection with Other Tick Borne Pathogens in Ticks - Raileanu, Cristian; Moutailler, Sara; Pavel, Ionuţ; Porea, Daniela; Mihalca, Andrei D.; Savuta, Gheorghe; Vayssier-Taussat, Muriel (Frontiers in Cellular and Infection Microbiology, 2017)
Identifying Borrelia burgdorferi as the causative agent of Lyme disease in 1981 was a watershed moment in understanding the major impact that tick-borne zoonoses can have on public health worldwide, particularly in Europe and the USA. The medical importance of tick-borne diseases has long since been acknowledged, yet little is known regarding the occurrence of emerging tick-borne pathogens such as Borrelia spp., Anaplasma phagocytophilum, Rickettsia spp., Bartonella spp., “Candidatus Neoehrlichia mikurensis”, and tick-borne encephalitis virus in questing ticks in Romania, a gateway into Europe. The objective of our study was to identify the infection and co-infection rates of different Borrelia genospecies along with other tick-borne pathogens in questing ticks collected from three geographically distinct areas in eastern Romania. We collected 557 questing adult and nymph ticks of three different species (534 Ixodes ricinus, 19 Haemaphysalis punctata, and 4 Dermacentor reticulatus) from three areas in Romania. We analyzed ticks individually for the presence of eight different Borrelia genospecies with high-throughput real-time PCR. Ticks with Borrelia were then tested for possible co-infections with Anaplasma phagocytophilum, Rickettsia spp., Bartonella spp., “Candidatus Neoehrlichia mikurensis”, and tick-borne encephalitis virus. Borrelia spp. was detected in I. ricinus ticks from all sampling areas, with global prevalence rates of 25.8%. All eight Borrelia genospecies were detected in I. ricinus ticks: Borrelia garinii (14.8%), B. afzelii (8.8%), B. valaisiana (5.1%), B. lusitaniae (4.9%), B. miyamotoi (0.9%), B. burgdorferi s.s (0.4%), and B. bissettii (0.2%). Regarding pathogen co-infection 64.5% of infected I. ricinus were positive for more than one pathogen. Associations between different Borrelia genospecies were detected in 9.7% of ticks, and 6.9% of I. ricinus ticks tested positive for co-infection of Borrelia spp. with other tick-borne pathogens. The most common association was between B. garinii and B. afzelii (4.3%), followed by B. garinii and B. lusitaniae (3.0%). The most frequent dual co-infections were between Borrelia spp. and Rickettsia spp., (1.3%), and between Borrelia spp. and “Candidatus Neoehrlichia mikurensis” (1.3%). The diversity of tick-borne pathogens detected in this study and the frequency of co-infections should influence all infection risk evaluations following a tick bite.